2015
DOI: 10.1111/1753-0407.12286
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of umbilical cord blood cells for type 1 diabetes mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is a chronic disorder that results from autoimmune-mediated destruction of pancreatic islet β-cells. However, to date, no conventional intervention has successfully treated the disease. The optimal therapeutic method for T1DM should effectively control the autoimmunity, restore immune homeostasis, preserve residual β-cells, reverse β-cell destruction, and protect the regenerated insulin-producing cells against re-attack. Umbilical cord blood is rich in regulatory T (T(reg)) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 114 publications
(258 reference statements)
0
9
0
1
Order By: Relevance
“…However, it is notable that cell‐based therapies aiming to replace β‐cells or targeting immune cells to restore immune balance have now been proposed as novel strategies and achieved beneficial effects. Clinical trials on regulatory T (T reg ) cells, hematopoietic stem cells, mesenchymal stem cells, and cord blood‐derived multipotent stem cells have revealed their disease‐modulating efficiency, with the outcomes suggesting that infusion of T reg cells or stem cells could prolong clinical remission or delay the development of T1D. In addition, it has been reported that adult fibroblasts generated from T1D patients can be reprogrammed with three transcription factors and transformed into T1D‐specific induced pluripotent stem (iPS) cells that can be differentiated into insulin‐producing cells .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is notable that cell‐based therapies aiming to replace β‐cells or targeting immune cells to restore immune balance have now been proposed as novel strategies and achieved beneficial effects. Clinical trials on regulatory T (T reg ) cells, hematopoietic stem cells, mesenchymal stem cells, and cord blood‐derived multipotent stem cells have revealed their disease‐modulating efficiency, with the outcomes suggesting that infusion of T reg cells or stem cells could prolong clinical remission or delay the development of T1D. In addition, it has been reported that adult fibroblasts generated from T1D patients can be reprogrammed with three transcription factors and transformed into T1D‐specific induced pluripotent stem (iPS) cells that can be differentiated into insulin‐producing cells .…”
Section: Resultsmentioning
confidence: 99%
“…Then the EPC-Exos was applied to repair diabetic chronic wounds. UCB can be collected during labor, with the distinct advantages of no risk to the donors, minimal ethical concerns, a low incidence of graft-versus-host disease and easy accessibility 22. UCB-derived MSCs have already been transplanted to improve islet function in patients with T2D 23.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, stem cells have emerged as powerful tools to improve skin wound healing. Human umbilical cord blood (UCB) is an attractive source of transplantable stem cells for wound repair, and posesses several distinct advantages of no risk to donors, easy accessibility, and a low incidence of graft-versus-host disease 5 , 6 . However, the direct use of stem cells for therapeutic purposes remains limited by many risk factors such as tumor formation, thrombosis, and unwanted immune responses 7 - 9 .…”
Section: Introductionmentioning
confidence: 99%